2005
DOI: 10.1248/cpb.53.653
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of β-Carbolinium Cations as New Antimalarial Agents Based on π-Delocalized Lipophilic Cation (DLC) Hypothesis

Abstract: Several b b-carbolines including naturally occurring substances and their corresponding cationic derivatives were synthesized and evaluated for antimalarial (antiplasmodial) activity in vitro and in vivo. A tetracyclic carbolinium salt was elucidated for antileishmanial and antitrypanosomal activities in vitro as well as antiplasmodial activity. Quarternary carbolinium cations showed much higher potencies in vitro than electronically neutral b b-carbolines and a good correlation was observed between p p-deloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…Therefore, we decided to follow the procedure of Takasu et al and adapt a Pictet-Spengler reaction for ring closure (Scheme 1). 4 Tryptamine was used as starting material and underwent a Pictet-Spengler reaction with ethyl glyoxylate followed by direct oxidative aromatization catalyzed with Pd/C to give kumujian A (3) (42%). Aldol condensation using sodium bis(trimethylsilyl)amide (NaHMDS) and ethyl acetate (EA) produced an acetate carbanion, which reacted with 3 to give 4. result a tautomeric enolate anion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we decided to follow the procedure of Takasu et al and adapt a Pictet-Spengler reaction for ring closure (Scheme 1). 4 Tryptamine was used as starting material and underwent a Pictet-Spengler reaction with ethyl glyoxylate followed by direct oxidative aromatization catalyzed with Pd/C to give kumujian A (3) (42%). Aldol condensation using sodium bis(trimethylsilyl)amide (NaHMDS) and ethyl acetate (EA) produced an acetate carbanion, which reacted with 3 to give 4. result a tautomeric enolate anion.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism explaining the damaging effect of DES on microorganisms may be associated to their interactions with the cellular membranes. This greater DES 0 anti-bacterial activity compare to that of their individual constituents, may be attributed to the charge delocalization through the hydrogenbonding between the anion and the HBD, a mechanism similar to the antimicrobial activity of well-observed Delocalized Lipophilic Cations (DLC) [26,27].…”
Section: From Eutectic To Deep Eutectic Solvents (Des)mentioning
confidence: 97%
“…Improvements in the Antimalarial Activities of the Natural Alkaloids Using the DLC Hypothesis 35,36) The β-carboline alkaloids are widely found in a number of plants. Some of these alkaloids exhibit a variety of biological and pharmaceutical potencies including antimalarial activity [37][38][39][40] (Fig.…”
Section: )mentioning
confidence: 99%
“…This study demonstrated that the transformation into a DLC structure could prove to be a highly effective modified method for preparing and designing antimalarial compounds. 35,36) …”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation